2007
DOI: 10.1038/sj.sc.3102155
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes after spinal cord tumor resection in the United States from 1993 to 2002

Abstract: Study design: Retrospective cohort study. Objective: Data on patient outcomes after surgery for spinal cord tumors have been derived from single-institution series. The objective of this study is to report inpatient complications, mortality and outcomes on a national level. Setting: United States, national inpatient care database. Methods: The National Inpatient Sample (NIS) was used to identify 19 017 admissions for resection of a spinal cord tumor in the United States from 1993 to 2002. The effects of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 14 publications
4
47
0
Order By: Relevance
“…16 Similarly, compared with the results of an earlier study of surgically treated SCTs in the US between 1993 and 2002, the total complication rate and mean length of stay decreased from 17.5% and 7.2 days, respectively, in 1993-2002 to 4.2% and 6.39 days in 2002-2010. The number of patients has remained the same during the study period despite an increase in the number of reporting hospitals, which is in accordance with the previous study.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…16 Similarly, compared with the results of an earlier study of surgically treated SCTs in the US between 1993 and 2002, the total complication rate and mean length of stay decreased from 17.5% and 7.2 days, respectively, in 1993-2002 to 4.2% and 6.39 days in 2002-2010. The number of patients has remained the same during the study period despite an increase in the number of reporting hospitals, which is in accordance with the previous study.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study, Patil et al 16 reported the incidence of complications and outcomes following SCT surgery between 1993 and 2002; however, there is no study focusing on the demographic and hospital-related factors that can affect the discharge disposition and cost of hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with private insurance are assumed to have better primary care access, which contributes to better maintenance of medical conditions. To this effect, our data show that patients with private insurance had a lower 57 found that age greater than 64 years had an increasingly significant association with postoperative adverse outcome. Sharma et al 61 also observed a higher likelihood of an adverse event in middle-aged and elderly patients after SCT surgery.…”
Section: Discussionmentioning
confidence: 73%